2021
DOI: 10.1021/acs.est.0c05875
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aeration on Mn(II) Sorbed to Clay Minerals and Its Impact on Cd Retention

Abstract: Manganese is a redox-sensitive element in soils and sediments that plays an important role in the retention of trace elements. Under anoxic conditions, clay minerals were shown to increase Cd retention by favoring the precipitation of Mn­(II) phases. In this study, we investigated the influence of aeration on anoxically formed Mn solid phases and its impact on Cd retention in the presence of two clay minerals with low Fe contents, a natural kaolinite (KGa-1b) and a synthetic montmorillonite (Syn-1). Ca-saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…During oxygenation, exchangeable Cd increased and both Fe mineral-bound Cd and PC-bound Cd decreased (Figure b), which might be partially ascribed to the decrease in pH (Figure S6). Previous studies demonstrated that the decrease of pH during oxygenation resulted in Cd release from Fe–Mn (oxyhydr)­oxides, , and low pH decreased Cd adsorption on biochar . The structure of PC was analyzed after oxygenation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During oxygenation, exchangeable Cd increased and both Fe mineral-bound Cd and PC-bound Cd decreased (Figure b), which might be partially ascribed to the decrease in pH (Figure S6). Previous studies demonstrated that the decrease of pH during oxygenation resulted in Cd release from Fe–Mn (oxyhydr)­oxides, , and low pH decreased Cd adsorption on biochar . The structure of PC was analyzed after oxygenation.…”
Section: Resultsmentioning
confidence: 99%
“…Drainage of paddy soils during the grain filling period results in the mobilization of Cd in soils and subsequent accumulation of Cd in rice grain. Cd mobilization is attributed to either oxidative dissolution of Cd sulfides or a decrease of pH induced by the precipitation of Fe (oxyhydr)­oxides. ,, As a consequence, many mitigation strategies are proposed to reduce Cd bioavailability, such as amendment of lime to improve soil pH, and prolonged the flooding time to reduce soil oxidation . Cd release is virtually due to the depletion of binding sites.…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the recent development of an atomic-resolution transmission electron microscope (AC-TEM) and X-ray absorption fine structure (XAFS), direct visualization of single atoms has become feasible and regular. More adsorption dynamic details, which might be ignored with traditional empirical adsorption models, could be directly visible now. These advancements, together with other techniques, provide an excellent opportunity to directly visualize the adsorption behavior on a material surface and open a new era to study the adsorption dynamics on the material interface.…”
Section: Introductionmentioning
confidence: 99%